The Impact of AUN-QA Certification on Strengthening Internal Quality Assurance Systems in Indonesian Higher Education: A Comparative Study of Mechanical Engineering Programs - Prihatiningsih, Titi Savitri; Supartono, Wahyu; Fitriyani, Fitriyani (Global Educational Research Review, 2024)
Purpose –  This study aims to evaluate the impact of AUN-QA (ASEAN University Network-Quality Assurance) certification on strengthening Internal Quality Assurance Systems (SPMI) in Indonesian higher education institutions, specifically in relation to aligning educational outcomes with industry needs. Given Indonesia’s global competitiveness ranking and challenges in aligning higher education with labor market demands, the research focuses on how AUN-QA certification affects quality assurance practices at the program level, aiming to close methodological and empirical gaps in the literature on quality assurance in Indonesian universities. Methods/Design/Approach – A comparative case study approach is used, focusing on two Mechanical Engineering programs at Universitas Gadjah Mada (UGM) and Universitas Sebelas Maret (UNS), which have and have not attained AUN-QA certification. Qualitative data collection was conducted through semi-structured interviews and document analysis, with participants involved in SPMI implementation. Thematic analysis was employed to identify patterns and themes regarding understanding, implementation, and commitment to SPMI and its alignment with industry needs. Findings – AUN-QA certification enhances the effectiveness of SPMI, promoting better alignment between educational outcomes and industry demands. UGM's certified program showed significant improvements in curriculum development, student outcome measurement, and stakeholder engagement compared to the non-certified program at UNS. However, challenges remain in fully integrating international standards into SPMI practices.. Originality/Value – This study provides empirical evidence on the positive impact of international certification on quality assurance in Indonesian higher education, offering insights into how AUN-QA certification can drive continuous quality improvement and closer alignment with industry expectations, addressing gaps in both theoretical and practical knowledge. Practical Implications – The findings suggest that higher education institutions should prioritize internal quality assurance alongside international certification to produce industry-relevant graduates. Policymakers and university administrators are encouraged to support the adoption of AUN-QA and similar certifications to enhance the global competitiveness of Indonesian graduates.. Keywords AUN-QA certification, internal quality assurance, higher education, industry alignment, curriculum development, Indonesia Paper type Research paper